2011
DOI: 10.1007/s00262-011-0972-z
|View full text |Cite
|
Sign up to set email alerts
|

The absence of B lymphocytes reduces the number and function of T-regulatory cells and enhances the anti-tumor response in a murine tumor model

Abstract: Increasing evidence suggests that B lymphocytes play a central role in inhibiting the immune response against certain tumors, but the underlying mechanisms by which B cells facilitate tumor growth are still poorly understood. In this study, we investigated how the presence or absence of B cells affects expansion and function of T-regulatory cells ('T-regs') in a murine breast tumor model (EMT-6). We compared tumor growth, and the number and function of T-reg cells in wild-type immune-competent mice (ICM) and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
76
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(79 citation statements)
references
References 33 publications
3
76
0
Order By: Relevance
“…7 These studies showed that growth of cancer cells could be limited without metastasis in B-cell-deficient mice. 8 In addition, a subset of B cells with negative regulatory function were identified as IL-10-competent B cells (or B10) which produces IL-10 upon stimulation. [9][10][11] Recently, Blair et al reported that CD19 C…”
Section: Introductionmentioning
confidence: 99%
“…7 These studies showed that growth of cancer cells could be limited without metastasis in B-cell-deficient mice. 8 In addition, a subset of B cells with negative regulatory function were identified as IL-10-competent B cells (or B10) which produces IL-10 upon stimulation. [9][10][11] Recently, Blair et al reported that CD19 C…”
Section: Introductionmentioning
confidence: 99%
“…B cells can also promote expansion of Tregs within the tumor bed, and antibody depletion of CD25 + T cells restores anti-tumor response (7). The percentage and absolute number of Tregs in the spleen and tumor bed are increased in wild-type (WT) mice compared with BCDM, and the Treg suppressive function is reduced in the absence of B cells (6). The adoptive transfer of B cells also restores tumor growth independently of the ability of those B cells to secrete IL-10 or to express CD40 (5, 7).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of murine tumors are either completely rejected or demonstrated reduced growth in the absence of B cells, including the EL-4 thymoma, MC38 colon carcinoma and the EMT-6 breast carcinoma, D5 mouse melanoma (5)(6)(7)(8). These tumors show reduced growth or are rejected in B-celldeficient mice (BCDM), and growth is restored following reconstitution with adoptively transferred B cells (5,7).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, novel studies focusing on the role of B cells as negative modulators of the antitumor response are currently underway. Evidence that accounts for the role of B cells in tumor-induced immunosuppression includes the existence of human B cells with a regulatory phenotype in solid tumors (11), the B cell-mediated induction of Tregs expansion (12)(13)(14) and the increase of tumor growth (12,(15)(16)(17). Methylcolanthrene-induced murine fibrosarcoma (MCC) is a highly immunogenic tumor that elicits an early specific antitumor immune reaction, which is not strong enough to impede tumor growth (18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%